2002
DOI: 10.1053/jhep.2002.32533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the MAPK and PI3K pathways enhances UDCA-induced apoptosis in primary rodent hepatocytes

Abstract: The mechanisms by which bile acids induce apoptosis in hepatocytes and the signaling pathways involved in the control of cell death are not understood fully. Here, we examined the impact of mitogen-activated protein kinase (MAPK) and phosphatidyl inositol 3-kinase (PI3K) signaling on the survival of primary hepatocytes exposed to bile acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 46 publications
5
100
0
4
Order By: Relevance
“…45,46 Pro-apoptotic activity of UDCA was also demonstrated in hepatocytes. 47 Although the mechanisms driving tumor suppressive activity are not fully understood yet, the tumor suppressive activity of UDCA is explained by its potential to activate pro-apoptotic mechanisms, inhibit the cell cycle, or prevent oncogenic factors. In addition, the anti-inflammatory action of UDCA has been suggested to be a crucial mechanism underlying treatment of various disorders, including cancer, primary sclerosing cholangitis and inflammation in symptomatic gallbladders with cholesterol gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Pro-apoptotic activity of UDCA was also demonstrated in hepatocytes. 47 Although the mechanisms driving tumor suppressive activity are not fully understood yet, the tumor suppressive activity of UDCA is explained by its potential to activate pro-apoptotic mechanisms, inhibit the cell cycle, or prevent oncogenic factors. In addition, the anti-inflammatory action of UDCA has been suggested to be a crucial mechanism underlying treatment of various disorders, including cancer, primary sclerosing cholangitis and inflammation in symptomatic gallbladders with cholesterol gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…1,38 A recent study showed that UDCA, via activation of the epidermal growth factor receptor and MAPK, induces a survival signal in hepatocytes that may contribute to the antiapoptotic effect. 39 Although intriguing, the impact of antiapoptotic mechanisms for the beneficial effects of UDCA in cholestatic liver disease remains unclear at present.…”
Section: Protection Against Bile Acid-induced Apoptosismentioning
confidence: 99%
“…4 Recently, we reported that treatment of primary rodent or human hepatocytes with deoxycholic acid (DCA) caused ligand-independent activation of ERBB1 (EGF receptor), which was responsible for activation of the ERK1/2 and AKT pathways. [5][6][7] In addition to ERBB1, bile acids also have been shown to induce ligand-independent activation of the insulin receptor, but not the insulin-like growth factor 1 receptor, in primary rodent hepatocytes. 8 Activation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) pathway by DCA was more strongly linked to activation of the insulin receptor than to ERBB1.…”
mentioning
confidence: 99%